Adult Ileo- Ileal Intussusceptions- A Rare Variety in Intestinal Obstruction (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Intussusceptions of bowel is more frequent in children but in adult it is less. Generally adult intussusceptions carry the risk of malignancy. So treatment option is not similar with pediatric variety. A female of 40 years was admitted with severe intractable pain, vomiting but no malena. Ultrasonographic findings and CT scan of abdomen suggested that the lesion could be of bowel origin. After resuscitation the patient was managed surgically and with good outcome.J Bangladesh Coll Phys Surg 2014; 32: 99-101